A systematic review and thematic synthesis of quality of life in the informal carers of cancer patients with cachexia. (February 2016) - Wheelwright, Sally; Darlington, Anne-Sophie; Hopkinson, Jane B; Fitzsimmons, Deborah; Johnson, Colin
Background: Informal carers of cancer patients with cachexia face additional challenges to those encountered by informal carers in general because of the central role food and eating play in everyday life. Patient weight loss and anorexia, core features of cancer cachexia, are frequent causes of distress in caregivers. Identification of quality of life issues can inform the development of interventions for both caregivers and patients and facilitate communication with healthcare professionals. Aim: To identify quality of life issues that are relevant to carers of cancer patients with cachexia. Design: A systematic review and thematic synthesis of the qualitative literature were conducted. Reporting followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data sources: PubMed, ISI Web of Knowledge, EMBASE, MEDLINE, CINAHL, PsycINFO and PsycARTICLES were searched for publications dated from January 1980 to February 2015 using search terms relating to cancer, cachexia, quality of life and carers. Papers written in the English language, featuring direct quotes from the carers of adult patients with any cancer diagnosis and cachexia or problems with weight loss or anorexia, were included. Results: Five themes were extracted from the 16 identified studies. These highlighted the impact on everyday life, the attempts of some carers to take charge, the need for healthcare professional's input, conflict with the patient and negative emotions. Conclusion: The complexity of caring for a cancer patient with cachexia translates into a range of problems and experiences for informal carers. By addressing the impact of caring for a patient with cancer cachexia on carers, both caregiver and patient quality of life may improve.